Piper sarmentosum Promotes Endothelial Nitric Oxide Production by Reducing Asymmetric Dimethylarginine in Tumor Necrosis Factor-α-Induced Human Umbilical Vein Endothelial Cells - Sundar, Uma Mahgesswary; Ugusman, Azizah; Chua, Hui Kien; Latip, Jalifah; Aminuddin, Amilia (Frontiers in Pharmacology, 2019)
Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of endothelial nitric oxide synthase (eNOS). ADMA is degraded by dimethylarginine dimethylaminohydrolase (DDAH). Elevated level of ADMA leads to reduction in nitric oxide (NO) production that is linked to endothelial dysfunction and atherosclerosis. Piper sarmentosum is an herb that has shown stimulation on endothelial NO production by increasing both expression and activity of eNOS. Thus, this study determined whether the positive effect of P. sarmentosum on NO production is related to its modulation on the DDAH-ADMA pathway in cultured human umbilical vein endothelial cells (HUVEC) exposed to tumor necrosis factor-α (TNF-α). HUVEC were divided into four groups: control, treatment with 250 µg/mL of aqueous extract of P. sarmentosum leaves (AEPS), treatment with 30 ng/mL of TNF-α and concomitant treatment with AEPS and TNF-α for 24 hours. After treatments, HUVEC were collected to measure DDAH 1 mRNA expression using quantitative real time polymerase chain reaction. DDAH 1 protein level was measured using enzyme-linked immunosorbent assay (ELISA) and DDAH enzyme activity was measured using colorimetric assay. ADMA concentration was measured using ELISA and NO level was measured using Griess assay. Compared to control, TNF-α-treated HUVEC showed reduction in DDAH 1 mRNA expression (P < 0.05), DDAH 1 protein level (P < 0.01) and DDAH activity (P < 0.05). Treatment with AEPS successfully increased DDAH 1 mRNA expression (P < 0.05), DDAH 1 protein level (P < 0.01) and DDAH activity (P < 0.05) in TNF-α-treated HUVEC. Treatment with TNF-α caused an increase in ADMA level (P < 0.01) and a decrease in endothelial NO production (P < 0.001). Whereas treatment with AEPS was able to reduce ADMA level (P < 0.01) and restore NO (P < 0.001) in TNF-α-treated HUVEC. The results suggested that AEPS promotes endothelial NO production by stimulating DDAH activity and thus reducing ADMA level in TNF-α-treated HUVEC.